2013
DOI: 10.4028/www.scientific.net/amr.689.22
|View full text |Cite
|
Sign up to set email alerts
|

Approach to Calibrated Simulation Tool for Improved Building Performance

Abstract: Simulation tools represent continuous, stochastic processes in buildings by discrete time-step, deterministic model estimations. All models make assumptions when representing real buildings. Detailed models more closely represent the operation of the real building and allow Energy Conservation Measures (ECM) to be investigated at finer resolution, using fewer assumptions. This paper presents a systematic, evidence-based approach to calibrated simulation. This approach yields a calibrated model that is based so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…Thus, over the years, hundreds of POE studies have been carried out on a variety of facilities. In POE studies, tools are developed based on the conditions of the case studies, and the evaluation criteria required by code, or the respective government agency in the building’s location (Shika et al , 2014). Researchers group the applicable performance elements into different categories, however careful study shows that they can be grouped under the three main categories suggested by Preiser et al (1988).…”
Section: On the Performance Of Academic Buildingsmentioning
confidence: 99%
“…Thus, over the years, hundreds of POE studies have been carried out on a variety of facilities. In POE studies, tools are developed based on the conditions of the case studies, and the evaluation criteria required by code, or the respective government agency in the building’s location (Shika et al , 2014). Researchers group the applicable performance elements into different categories, however careful study shows that they can be grouped under the three main categories suggested by Preiser et al (1988).…”
Section: On the Performance Of Academic Buildingsmentioning
confidence: 99%